1976
DOI: 10.1139/m76-130
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation in the muskeg ecosystem of the James Bay Lowlands, Northern Ontario

Abstract: The acetylene-reduction assay was used for in situ and laboratory assessment of biological nitrogen fixation in the acidic, waterlogged, muskeg ecosystem of the southern James Bay area, in the region of Moosonee, Ontario. In situ assays and subsequent laboratory experimentation revealed that nitrogenase activity was predominately a function of the activities of heterocystic blue-green bacteria associated with surface water, with the phyllosphere of mosses, and with at least one lichen, a species of Peltigera. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

1978
1978
1997
1997

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…For instance, numerous studies on N fixation in peat have shown highly variable results reflecting the different agents of fixation that may predominate and the different strata of peat sampled (Waughman andBellamy 1972, 1980;Dooley and Houghton 1973;Granhall and Selander 1973;Granhall and Lid-Torsvik 1975;Blasco and Jordan 1976;Alexander et al 1978; Barsdate and Alexander 1975;Dierberg and Brezonik 1981;Chapman and Hemond 1982). Most studies on N fixation and denitrification in peat (e.g., Granhall 1970;Waughman andBellamy 1972, 1980;Kallio and Kallio 1975;Granhall and Hofsten 1976;Waughman 1976;Basilier et al 1978;Muller et al 1980) have consisted of short-term measurements in the laboratory with small quantities of moss or subsurface peat.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, numerous studies on N fixation in peat have shown highly variable results reflecting the different agents of fixation that may predominate and the different strata of peat sampled (Waughman andBellamy 1972, 1980;Dooley and Houghton 1973;Granhall and Selander 1973;Granhall and Lid-Torsvik 1975;Blasco and Jordan 1976;Alexander et al 1978; Barsdate and Alexander 1975;Dierberg and Brezonik 1981;Chapman and Hemond 1982). Most studies on N fixation and denitrification in peat (e.g., Granhall 1970;Waughman andBellamy 1972, 1980;Kallio and Kallio 1975;Granhall and Hofsten 1976;Waughman 1976;Basilier et al 1978;Muller et al 1980) have consisted of short-term measurements in the laboratory with small quantities of moss or subsurface peat.…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen fixing potential was measured indirectly using the acetylene-ethylene technique (8,19,20). Laboratory studies involved aerobic incubation of samples in 60 ml serum vials or anaerobic incubation in Pankhurst tubes (21).…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory studies involved aerobic incubation of samples in 60 ml serum vials or anaerobic incubation in Pankhurst tubes (21). For in situ studies, replicate closed-type plastic canopies (8), were forced into the soil to provide an enclosed core 5 cm in height and with a surface area of 0.0082 m2, prior to affixing a bottom gas-tight plate and providing an atmosphere containing a final concentration of 10 acetylene. Incubation was in situ at prevailing surface temperature (24°-28°) Temperatures inside the canopies were 1 to 2° higher than the exterior soil surface temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotrophic potential was measured using "closed-type"plastic canopies (Blasco and Jordan 1976) Thornton's (1922) medium and ammonia and nitrite oxidizers on the medium of Matuleurck et al ( 1975) Boyd and Boyd (1971) and Bunnel etaL (1975) Counts of nitrogen-free agar (Table l) were high, but only l5-247o of the isolates from this medium were subsequently shown to fix N2 by the C2H2-C2Ha method (Blasco and Jordan 1976 For personal use only. (Bliss 1975) …”
mentioning
confidence: 99%